The Dying of a Principle: The Bending of Light, the Oppenheimer-Snyder Gravitational Contraction, and the Postulate of Relativity - Bender, Darrell (European Journal of Applied Sciences, 2025)
The first time one discovers by thinking about it that some great postulate is false because of a contradiction, an alarm bell rings, yet the propaganda that the postulate is true pervades in the face of obvious evidence that contradicts it. As far as figuring this out, most will just consider the postulate to be true. When the process involves every significant postulate at which one looks with corresponding propaganda too, the entities that control this are considered to be evil when the dumbing of the crowd is at hand. Years ago when we first considered the measured velocity of light in the moving system, we were aware that this matter had already been resolved beforehand by Einstein’s principles or postulates thinking that postulates in plain sight had to be true. We analyzed the case that follows in the abstract and blamed the problem that what we obtained for the velocity of light was not c on the Lorentz contraction since the postulated value for this velocity had to be c. Of course, the problem was not the Lorentz contraction, but Einstein’s principles, which were never true. The dying of Einstein’s principles, the one about the same laws of physics holding in systems that are in uniform translatory motion and the other, taken to be a law, about the velocity of light being the constant c, gives one access to the light of free thought, which was always suppressed. To quote Dylan Thomas, “Do not go gentle into that good night. Rage, rage against the dying of the light.”